Psychological Effectiveness of Play Accompanying Training Units in Developing Some Physical Traits in Soccer Goalkeepers at School Level in the Sulaymaniyah Governorate - اسعد, ديار كمال (Sulaimani Journal for Humanities, 2025)
Sports psychology is a science that has a direct impact on the development of performance level and development of players, which is looking at the physical and mental requirements of sports practice, and show its importance through the study, analysis and identification of sports behavior in all its aspects, the study is in the light of its mathematical goals as well as Dynamic interaction between psychological variables and variables of the sports environment, including physical characteristics, and through the experience of scientific researcher and being a goalkeeper coach for age groups and follow-up of some exercises Madras spherical note that the development of some physical abilities and skill is through physical exercises The research aimed to develop exercises using the psychology of play accompanying the training units in the development of some physical abilities, to identify the differences between the experimental and control groups in the post-tests of some physical abilities of the school school guards in the center of Sulaymaniyah province, the research community was determined from school goalkeepers Spherical in the center of the province of Sulaymaniyah and the number (28) goalkeeper representing (9) football school, and the sample of the research was selected from the schools (20) goalkeeper, then the sample was divided into two groups and randomly and by lottery, which is the way given to each person From the past With the same opportunity given to others, so each group consisted of (10) goalkeepers, and after excluding those who were selected for the exploratory experiment and the (8) goalkeepers.